Chemical Characterization, Antioxidant, and Antihyperglycemic Capacity of Ferulated Arabinoxylan Extracted from “Chicha de Jora” Bagasse: An Ancestral Fermented Beverage from Zea mays L. - Juan Jharol Segovia-Huarcaya; Lilian Silvana Valentin-Soto; Oscar Herrera-Calderon; César Máximo Fuertes-Ruitón; Josefa Bertha Pari-Olarte; Eddie Loyola-Gonzales; José Santiago Almeida-Galindo; José Francisco Kong-Chirinos; Elizabeth Julia Melgar-Merino; Mohammed Merae Alshahrani; Shafi Mahmud (Journal of Food Quality)
Bagasse is a byproduct generated during the process of making the traditional Andean drink named “chicha de jora” in Peru, which is a potential source for the extraction of ferulated arabinoxylan (FAX). The aim of this study was to extract and characterize the FAX from bagasse and determine its antioxidant and antihyperglycemic capacity in vitro. As a result, FAX of molecular weight ≥3.5 kDa presented moisture content, pH, total ash, proteins, and total phenolic content with values of 8.00%, 5.81, 2.68%, 3.78%, and 5.72 mg EAG/g, respectively. Thin-layer chromatography identified the monosaccharides L-arabinose and D-xylose. HPLC-MS/MS analysis of FAX confirmed the presence of methyl-pentofuranosides or methyl-pentopyranosides. The FT-IR spectrum presented characteristic bands of FAX. The FAX showed antioxidant capacity determined by the DPPH assay (IC50 = 6.59 mg/mL and TEAC = 7.7844 μmol/g sample), ABTS (IC50 = 6.50 mg/mL and TEAC 35.34 μmol/g sample), and FRAP (14.08 μmol AA/g and 36.63 μmol FeSO4/g). On the other hand, FAX showed glucose adsorption capacity, inhibition of glucose diffusion, and inhibition of the enzyme α-amylase (IC50 = 4.73 mg/mL). The results showed that the FAX extracted from the bagasse generated during the production of the “chicha de jora” has in vitro antioxidant and antihyperglycemic capacity.